p+1p+2=1,p+1p+2=1,p + \frac{1}{{p + 2}} = 1{\text{,}}   Find the value of (p+2)3" role="presentation">(p+2)3(p+2)3{\left( {p + 2} \right)^3}  + 1(p+2)3" role="presentation">1(p+2)31(p+2)3\frac{1}{{{{\left( {p + 2} \right)}^3}}}  - 3 = ?" /> p+1p+2=1,p+1p+2=1,p + \frac{1}{{p + 2}} = 1{\text{,}}   Find the value of (p+2)3" role="presentation">(p+2)3(p+2)3{\left( {p + 2} \right)^3}  + 1(p+2)3" role="presentation">1(p+2)31(p+2)3\frac{1}{{{{\left( {p + 2} \right)}^3}}}  - 3 = ?" /> p+1p+2=1,p+1p+2=1,p + \frac{1}{{p + 2}} = 1{\text{,}}   Find the value of (p+2)3" role="presentation">(p+2)3(p+2)3{\left( {p + 2} \right)^3}  + 1(p+2)3" role="presentation">1(p+2)31(p+2)3\frac{1}{{{{\left( {p + 2} \right)}^3}}}  - 3 = ?" />

p+1p+2=1,
  Find the value of
(p+2)3
  +
1(p+2)3
  - 3 = ?

  • 112
  • 216
  • 318
  • 415
Answer:- 1
Explanation:-

Solution:
p+1p+2=1, Find the value of (p+2)3+1(p+2)33Adding2on both sides(p+2)+1(p+2)3Taking cube on both sides(p+2)3+1(p+2)3+3(p+2)×1(p+2)[(p+2)+1(p+2)]=[(p+2)+1(p+2)]3[(p+2)+1(p+2)]=33[(p+2)+1(p+2)]=27(p+2)3+1(p+2)3+9=27(p+2)3+1(p+2)3=18According to the question,183=15

Post your Comments

Your comments will be displayed only after manual approval.

  Find the value of
(p+2)3
  +
1(p+2)3
  - 3 = ?", "text": "
p+1p+2=1,
  Find the value of
(p+2)3
  +
1(p+2)3
  - 3 = ?", "dateCreated": "7/24/2019 10:09:12 AM", "author": { "@type": "Person", "name": "Nitin Sir" }, "answerCount": "4", "acceptedAnswer": { "@type": "Answer", "text": "
Solution:
p+1p+2=1, Find the value of (p+2)3+1(p+2)33Adding2on both sides(p+2)+1(p+2)3Taking cube on both sides(p+2)3+1(p+2)3+3(p+2)×1(p+2)[(p+2)+1(p+2)]=[(p+2)+1(p+2)]3[(p+2)+1(p+2)]=33[(p+2)+1(p+2)]=27(p+2)3+1(p+2)3+9=27(p+2)3+1(p+2)3=18According to the question,183=15
", "dateCreated": "7/24/2019 10:09:12 AM", "author": { "@type": "Person", "name": "Nitin Sir" } }, "suggestedAnswer": { "@type": "Answer", "text": "
Solution:
p+1p+2=1, Find the value of (p+2)3+1(p+2)33Adding2on both sides(p+2)+1(p+2)3Taking cube on both sides(p+2)3+1(p+2)3+3(p+2)×1(p+2)[(p+2)+1(p+2)]=[(p+2)+1(p+2)]3[(p+2)+1(p+2)]=33[(p+2)+1(p+2)]=27(p+2)3+1(p+2)3+9=27(p+2)3+1(p+2)3=18According to the question,183=15
", "dateCreated": "7/24/2019 10:09:12 AM" } }
Test
Classes
E-Book